Professional Learning Communities in the Contemporary Basic Education in Finland - Suwalska, Arleta (Rocznik Pedagogiczny, 2020)
In the article I will pay attention to schools as Professional Learning Communities which include: shared values and vision of education, collective responsibility, reflective professional inquiry, col- laboration and group, as well as individual, learning. I also analyze trust and respect, closely related to PLC in contemporary Finnish education.